1989
DOI: 10.3109/07420528909056930
|View full text |Cite
|
Sign up to set email alerts
|

Season-Of-Birth and Acute Leukemia of Infancy

Abstract: Because of its short and clearly delineated latency period, acute leukemia of infancy is particularly suited to etiologic analysis. From 1950 to mid-1985, 31 infants with acute leukemia (less than 1 year of age) were registered at the University of Texas, M.D. Anderson Cancer Center at Houston. The medical records of these infants were reviewed for demographic and birth information. Of the 31 infants, 14 (45%) were Hispanic. The sex ratio was 3:1 male/female) for white infants and 5:9 for Hispanic infants. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…9,10 This ovopathy concept is backed by animal experiments on preovulatory and postovulatory overripeness ovopathy and in line with the disproportional excess rates of fatal neural tube defects 11 and type 1 diabetes mellitus, 12 which increase further away from the equator and diverge on both hemispheres. This proposed causal relation of seasonally bound nonoptimally matured oocytes to cancer, therefore, not only agrees with the geographical latitude effect under discussion but also with the disproportional month-of-birth deviations apparent in childhood leukaemia, [13][14][15] premenopausal breast cancer, [16][17][18] lung cancer, 19 and brain tumours in children 20,21 and adults. 22 These deviations in general correspond with the major total birth peak or major ovulatory season.…”
supporting
confidence: 66%
“…9,10 This ovopathy concept is backed by animal experiments on preovulatory and postovulatory overripeness ovopathy and in line with the disproportional excess rates of fatal neural tube defects 11 and type 1 diabetes mellitus, 12 which increase further away from the equator and diverge on both hemispheres. This proposed causal relation of seasonally bound nonoptimally matured oocytes to cancer, therefore, not only agrees with the geographical latitude effect under discussion but also with the disproportional month-of-birth deviations apparent in childhood leukaemia, [13][14][15] premenopausal breast cancer, [16][17][18] lung cancer, 19 and brain tumours in children 20,21 and adults. 22 These deviations in general correspond with the major total birth peak or major ovulatory season.…”
supporting
confidence: 66%
“…Vianna and Polan, 1976) have found a different significant peak in each of the age groups examined whilst others have failed to find seasonality in any age group (Bailar and Gurian, 1964;Stark and Mantel, 1967;Van Steensel-Moll et al, 1983). Perhaps of most interest with regard to age-specific analyses is our failure to find seasonal variation in the birth dates of infant leukaemias, an age-group in which previous studies have found significant seasonality (Ederer et al, 1965;Meltzer et al, 1989). We also found no evidence to support Stewart's hypothesis (1975) that a deficit of leukaemia cases may occur among babies born between July and December who are exposed to winter conditions during the first 6 months of life and are therefore more likely to die from respiratory infections before a diagnosis of leukaemia is made.…”
Section: Discussionmentioning
confidence: 75%
“…A significant association was found for winter season of birth and the incidence of ALL in 31 children less than one year of age in clinical series data obtained during the period 1950-1985. 24 However, as these data were not population-based and information on the seasonality of births in the population(s) from which they came was not available, the implications of these results may be questioned. A significant association between birth month and mortality among 961 children less than one year of age was found in data collected across the United States during the years 1950-1959.…”
Section: Discussionmentioning
confidence: 90%